BIOSURFACTANTS: SUSTAINABLE ALTERNATIVE TO SYNTHETIC SURFACTANTS AND THEIR APPLICATIONS - POOMALAI, PRAVEENA; KRISHNAN, JANESHA; RAVICHANDRAN, ASHWIN; SURESHKUMAR, RAMAN (International Journal of Applied Pharmaceutics, 2024)
Biosurfactants are surface active agents produced by microorganisms, which help reduce surface or interfacial tension between two immiscible liquids like oil and water. In recent years, Due to their environmentally friendly nature and wide range of applications in various industries, they can act as a sustainable alternative to synthetic surfactants. This review article provides an overview of biosurfactants, emphasizing their need for biosurfactants, the production process, and their classification based on molecular weight, charge, and the microorganism they derived. The advantages include biodegradability, biocompatibility, low toxicity, surface activity, and specificity, and various areas where the biosurfactant used are emulsification, thermal stability, pH stability, wetting ability, foaming ability, and spreadability. Research on using biosurfactants in various formulations like nanoparticles, liposomes, transdermal application, nanoemulsion, and nanocapsules is also highlighted in this review to support its application in the medical field. Biosurfactants are also utilized in various fields like the pharmaceuticals, cosmetics, food, and oil industries. However, they have their drawbacks, which include high production costs, variability in production yield, sensitivity to the environment, lack of standardization, hurdles in regulatory approval, and research and development limitations. Despite certain drawbacks, biosurfactant offers a sustainable alternative to synthetic surfactants.